PENGARUH PENDEKATAN PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Nur Rahmi Rizqi; Lilis Arini (Mahesa Research Center, 2020)
This study aims to determine the effect of problem-based learning approaches to improve students' mathematical communication skills. The study was conducted at SMP Negeri 1 Pangkalan Susu in the odd semester of the 2019/2020 school year with a population of all grade VII students and a sample of 30 students. The instrument uses a validated test. Both classes were given a post-test after treatment. Before testing the hypothesis, the requirements are normality test, it turns out that both data are normally distributed and the homogeneity test turns out to be both homogeneous data. From the results of hypothesis testing using the t-test obtained tcount (3.018)> ttable (1.671) where Ha is received. From the determination test results obtained 13.6% while 86.4% influenced by other factors. This means that there is an influence of the use of problem-based learning on mathematical communication skills of students of SMP Negeri 1 Pangkalan Susu.